National Day of the kingdom of Saudi Arabia During the Reign of King Faisal bin Abdulaziz Al Saud 1385-1395 Ah / 1964-1975 ad - Alshammary, Monerah Goful Matar (Journal of Posthumanism, 2025)
The research examines the national day of the Kingdom of Saudi Arabia during the tenure of King Faisal bin Abdulaziz Al Saud, focusing on the occasion designated as the national day, the involvement of official and public entities, the engagement of governmental and private organizations, the contributions of Saudi agencies, legations, and embassies, as well as the participation of Arab, Islamic, and allied nations.